Calculating pump performances using Visual Basic / Zaimi Saleh @ Yazid and Mohd Farid Che Nordin - Saleh @ Yazid, Zaimi; Che Nordin, Mohd Farid (2006)
With ‘Calculating Pump Performances Using Visual Basic’, we aim to give user a method that could simplify the task. Even though it is still early to design an advanced program, this tool should enable us to measure the basic calculation of pump performances. In this pilot project, we tried to invent something new in preparing our final project. By making this engineering application, we can start making new things that are not done yet. Visual Basic 6.0 is chosen as our programming language because it is easier to use and has better user interface. This program can simplify the process of finding the pump performances. After conducting some tests and finding alternative solutions, we managed to put up our effort to design this program. Visual Basic 6.0 is such a useful tool that can be easily used by other to create any applications.